Improving creative thinking skill of fluid dynamic through IBL-STEM with formative assessment - Permana, Gilang Adi (2021)
The concept of Dynamic Fluid is part of the Fluid Mechanics that underlies several phenomena and technologies in everyday life. Improving students' ability to think creatively is needed to prepare students for the challenges of the 21st Century. However, students' creative thinking skill are still low on dynamic fluid material, and the application of integrated STEM Inquiry with Formative Assessment (IBL-STEM with FA) solutions is still rare. This study aims to improve students' creative thinking skill and describe the difficulties of creative thinking on Dynamic Fluid material after IBL-STEM with FA. The mixed methods with an embedded experimental design used the research subjects of 34 students (M = 14 and F = 20) in class XI of state senior high schools in Jombang, Indonesia, selected by purposive sampling. This study used the Fluid Dynamics Creative Thinking Skill Test instrument in the form of 6 essay questions with a reliability of 0.869. The pretest and posttest quantitative data were analyzed by the Wilcoxon test, d effect, and N- gain. Whereas qualitative data on the variety of students' answers, and the results of interviews and observations were analyzed by coding, data reduction, and conclusion gathering. Variety of student answers was coded based on not creative, less creative, quite creative, creative, and very creative. The results showed that intervention significantly increased students' ability to think creatively with N-gain = 0.64 (medium category) and d-effect size = 5.05 (very large category). After learning, students were still experiencing difficulties to think flexibly both (1) developing tools based on continuity concept and (2) developing an effective and environmentally friendly chimney design. Also, students still have difficulty in original thinking to get high speed and widespread sprayers. Nevertheless, an increase in students' creative thinking on dynamic fluid material indicates that IBL-STEM with FA can be applied in learning.